The fairness of Hell. (22nd August 2019) - Hershenov, David B.
Abstract: The Christian conception of Hell as everlasting punishment for past sins is confronted with two charges of unfairness. The first is the inequity of an eternal punishment. The never‐ending punishment seems disproportionate to the finite sin (Kershnar, Lewis, Adams). A second and related problem is that the boundary between sins that send one for all eternity to Hell and those sins that are slightly less bad that are compatible with an eternity in Heaven is arbitrary and thus it is unfair that sinners so alike are treated differently (Sider). Hell, as traditionally conceived, is then claimed to be incompatible with God's traditional attributes such as his commitment to justice, omniscience and omnipotence. The unfairness can be avoided by appealing to God's foreknowledge and a debt/atonement theory of punishment. My view is analogous to refusing to parole the unrepentant. If a wrongdoer is eternally defiant, then he can never be released from Hell for his debt won't ever be paid if he isn't reformed and reconciled with the wronged. So it doesn't matter that his initial sin was a finite wrong not deserving of infinite punishment nor a sin no worse than that of the penitent in Heaven.